Interaktion im wissenschaftlichen Fachtext aus kontrastiver Sicht. Untersucht anhand von deutschen und lettischen linguistischen Aufsätzen - Agnese Dubova; Diāna Laiveniece; Dzintra Lele-Rozentāle (Linguistische Treffen in Wrocław)
Linguistic specialised communication can take place in various ways, and the ‘pure’ technical language formulations are combined with those used in everyday scientific language to enable interaction between the author and the addressee, as well as to direct it in a subject-oriented manner. Such interaction not only spans cross-disciplinary and cross-culturally, but is also culturally conditioned. In this paper, the significance of interactional discourse markers in German and Latvian linguistic papers is illustrated based on the conclusions, which contain the quintessence of professional intention. The aim is to determine whether the interaction between the writer and the reader in both languages/cultures is the same or different and whether the linguistic discourse, the corresponding discourse style within the scientific discipline, and the associated problematic cases can be examined in future research. The study is based on two parallel mini corpora of 30 linguistic papers each, which were published in electronic form in the period from 2020 to 2022. Papers representing German and Latvian as profiling languages were selected. The theoretical framework for this analysis is Ken Hyland’s model (2005). Discourse markers such as hedges, boosters, attitude markers, self mentions, and engagement markers that build a relationship with the reader are analysed. Differences in the usage of interactional discourse markers can be mainly seen as external to language processes. It is necessary to establish an empirical base for German-Latvian contrastive studies in the field of specialist texts and didactics so that it can be expanded and described in detail.